2019
DOI: 10.2478/fon-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles in employing evidence-based practice by nurses in their clinical settings: a descriptive study

Abstract: Objective The challenge of employing evidence-based practice (EBP) is multifarious and varied. Nursing interventions supported by research evidence have been exposed to progress positive patient outcomes, while its implementation is faced with various obstacles. This study aimed to identify obstacles in employing EBP by nurses in their clinical settings. Methods This descriptive design study was conducted at Benha University Hospital with a convenient sample of 154 nurses. Two tools were utilized: (I) sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Theses in line with Bashar [26] who reported that nurses who were more knowledgeable regarding EBP, had a greater positive attitude towards EBP and a stronger tendency to apply EBP. This result is in contrast with Karki et al [27] who reported that although this sample of Nepalese nurses and students had positive attitudes towards EBP, their knowledge and skills were limited, and there are many barriers to implementing EBP in Nepal.…”
Section: Relationship Between the Study Variablescontrasting
confidence: 94%
See 1 more Smart Citation
“…Theses in line with Bashar [26] who reported that nurses who were more knowledgeable regarding EBP, had a greater positive attitude towards EBP and a stronger tendency to apply EBP. This result is in contrast with Karki et al [27] who reported that although this sample of Nepalese nurses and students had positive attitudes towards EBP, their knowledge and skills were limited, and there are many barriers to implementing EBP in Nepal.…”
Section: Relationship Between the Study Variablescontrasting
confidence: 94%
“…Furthermore, EBP is a keystone for health care quality [26]. As nurses play a vital role in the delivery of health care and results of revised studies show nurses do not generally integrate research evidence in their daily practice [27]. The current study was conducted to assess the knowledge, perception and altitude regarding EBP among nurses working at King Abdullah Medical City, Makkah, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been studies of health professional experiences with patient falls in hospital [ 23 , 24 ], and health professional views of patient education [ 25 , 26 ], there has not yet been a study exploring health professional views about hospital patient falls education. A greater understanding of health professional views can help to facilitate implementation of evidence-based practice [ 27 , 28 ]. Identifying health professional views is necessary to facilitate a process where their needs are met and therefore lead to them being more willing to engage with implementing evidence-based approaches [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners have reported encountering several obstacles with the use of EBP in clinical practice ( 23 ). Many studies have found that insufficient knowledge about EBP, lack of time due to workload, level of academic qualifications and level of work experience were the main barriers to the use of EBP during clinical practice ( 24 28 ).…”
Section: Introductionmentioning
confidence: 99%